The percentiles ratio 20th to 5th of bending strength and stiffness distribution in the case of spanish softwoods - Nevado, Miguel A. Rz.; Arriaga, Francisco; Díez, Rafael (Maderas. Ciencia y Tecnología, 2025)
A group of databases making a total of approximately 9300 sawn timber pieces from Spanish coniferous species, tested according to European standards and visually graded mainly according Spanish standards were analyzed. The percentiles ratio 20th/5th of bending strength, modulus of elasticity and density distribution were obtained for different combinations of species and visual stress grade. The Eurocode 5 proposes this percentile ratio by a coefficient kfi which is used to determine the design values of mechanical properties in fire situation. The percentile ratios obtained were compared with the specified value in Eurocode 5 for solid timber (kfi = 1,25). In lower grades of Spanish coniferous timber, this value was overly conservative. A value of kfi of 1,4 seems to be more adequate for the case of the bending modulus of elasticity and 1,4 to 1,5 for the bending strength. It is noted that, in the case of the upper grades, this value should be of 1,3; close to the Eurocode proposal. Furthermore, in the case of density, the value should be of 1,1; hence lower than suggested in the code.